HIV Impairs CD34+- Derived Monocytic Precursor Differentiation into Functional Dendritic Cells. (July 2013) - Bordoni, V.; Castelli, G.; Montesoro, E.; Federico, M.; Sacchi, A.; Morsilli, O.; Agrati, C.; Martini, F.; Chelucci, C.
Dendritic cells (DCs) perform a basic role in the immune system by allowing the initiation of the primary T-cell-dependent immune response. Given previous indirect evidence that DC maturation and function are impaired by HIV, we have developed an in vitro culture system in order to verify the effect of HIV infection on DC function during the development from hematopoietic progenitors. Considering that monocytic (Mo) differentiating cells efficiently replicate monocytotropic HIV, we examined whether HIV-infected monocytic precursors (MoP) were able to generate functional DCs. CD34 + hematopoietic progenitor cells (HPCs) were induced along Mo differentiative pathway in liquid cultures and at an early stage of culture, MoP were infected with M-tropic BaL HIV strain, and after 2 days they were switched to DC differentiation with GM-CSF and IL-4. Derived DCs were actively infected, as detected by HIV-p24 production. HIV did not significantly affect cell viability, but induced a reduction in cell proliferation and an inefficient functional activity in terms of uptake capability and stimulation of allogenic T cells. These results indicate that HIV-infected MoP lost the capacity to generate functional DCs, and this may represent one of the many mechanisms of immunosuppression exploited by HIV.